2018
DOI: 10.1002/fedr.201700011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Colocynth (Citrullus colocynthis Schrader) Populations in the Eastern Desert of Egypt as Revealed by Morphological Variation and ISSR Polymorphism

Abstract: The analysis of variation in morphological traits differentiated Citrullus colocynthis populations growing north of Qena‐Quseir road (25°56'5.28”N to 28°11'40.56”N) from populations growing south of that road (25°0'55.80”N to 22°46'15.24”N). This differentiation is particularly associated with fewer number of shorter branches as well as longer days to flowering and fruiting. The ISSR polymorphism distinguished one population from all other populations, in agreement with its lowest percentage of polymorphic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The second included all colocynth ecotypes, except K10, which was grouped in the third cluster et al ( 2001) who with 30 RAPD grouped the two species in different clusters. The high percentage of polymorphism based on RAPD markers reported among ecotypes in this study, is in agreement with the high polymorphism found in C. colocynthis populations using ISSR markers (Badr et al 2018). Mujaju et al (2010) reported successful differentiation between two major groups of watermelon (Citrullus lanatus) landraces from Zimbabwe using RAPD and ISSR markers.…”
Section: Resultssupporting
confidence: 90%
“…The second included all colocynth ecotypes, except K10, which was grouped in the third cluster et al ( 2001) who with 30 RAPD grouped the two species in different clusters. The high percentage of polymorphism based on RAPD markers reported among ecotypes in this study, is in agreement with the high polymorphism found in C. colocynthis populations using ISSR markers (Badr et al 2018). Mujaju et al (2010) reported successful differentiation between two major groups of watermelon (Citrullus lanatus) landraces from Zimbabwe using RAPD and ISSR markers.…”
Section: Resultssupporting
confidence: 90%
“…The soil characteristics, particularly Na, Ca, K, Mg, Cl, SO 4 , pH, EC, gravels, and moisture contents, play essential roles in the vegetation groups in the Eastern Desert of Egypt [50]. The presence of some medicinal species in large groups of the Eastern Desert of Egypt reflects its capability to remain under various environmental systems [25,49]. In our study, A. javanica behaves in the same manner.…”
Section: Discussionmentioning
confidence: 53%
“…In Egypt, the main focus of the molecular diversity of five populations of Achillea fragrantissima using RAPD and isozymes markers showed that the variations in zonation were especially reflected on DNA fingerprinting [44]. Consequently, the populations of some species in the Eastern Desert of Egypt from close geographical sites were grouped together corroborating a limited gene flow that may be due to fragmentation of the geographical range in the species assured by Badr et al [25,45]. In the current study, the proportion of polymorphic bands distinctly specified that the ISSR markers are extremely polymorphic and particularly informational for determining genetic relationships of the examined A. javanica populations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation